NILAI INDEKS GLIKEMIK PRODUK OLAHAN GEMBILI (Dioscorea esculenta) - Rimbawan Rimbawan; Resita Nurbayani (Food and Nutrition Society of Indonesia, 2013)
The objective of this research was to analyze the glycemic index values of gembili products. The research consisted of three stages covered: (1) processing of gembili into three treatments (boiled, steamed, and fried), (2) analyzing of nutrient contents in gembili products, (3) measuring of glycemic index of three processed food. Moisture content (wet based/wb) in boiled, steamed and fried gembili were 68.09%, 62.11%, and 49.09% respectively. Ash content (dry based/db) in boiled, steamed and fried gembili were 1.62%, 2.15%, and 2.13% respectively. Fat content (dry based/db) were 0.63%, 0.37% and 7.75%, while protein content (dry based/db) were 3.71%, 2.99%, and 4.25%. Insoluble dietary fiber content (dry based/db) between 11.79% to 13.43%, while was higher than soluble dietary fiber content (dry based/db) between 5.84% to 10.88%. Total dietary fiber content (dry based/db) in boiled, steamed and fried gembili were 19.01%, 18.15%, and 24.30% respectively, while carbohydrate by difference content (dry based/db) were 91.05%, 93.33%, and 88.88% respectively. The results of this study indicated that all glycemic index values of gembili products were high (>70). Glycemic index values gembili boiled, steamed, and fried gembili were 85.56, 87.56, and 83.61 respectively. Analysis of variance test One Way ANOVA showed that those treatments did not significantly affect the glycemic index value (p> 0.05).